PENGARUH MODEL NUMBER HEAD TOGETHER TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPA DI SD - Bilhandi, Bilhandi; Rosnita, Rosnita; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyse the influence of model Number Head Together in the learning of Science against the results of the learning learners class V 24 State primary school East of Pontianak. The method used is an experiment with the form of a Quasi Experimental Design draft non equivalent control group design. The population of the entire learners from two classes totalling 51 people, the sample of this research is the learners class VB totalling 25 persons as class experiments and learners as a class VA class a control that add up to 26 people. Data collection techniques used are measurement techniques and data-collecting instrument is the written test multiple choice-shaped.Â Based on the analysis of data obtained average results post-test class experiment 80.02 and average post-test control of 74.42. Hypothesis test results using a t-test (Polled Variance) thitung = 3.248 obtained as for dk (26 + 25-2 = 49) with significant level Î± = 5% obtained ttabel = 1.676, meaning thitung > ttabel, then the Ha received, this proves there is influence model Number Head Together in the learning Sciences. Based on the results of the calculation of effect size (ES) obtained ES = 0.59 which included the criteria of being, namely 0.59 < 0.8. This it can be said that the application of the model Number Head Together in learning natural sciences provide positive influence towards learning outcomes learner class V 24-State primary school East of Pontianak.Â Keywords: influence, Model Number Head Together, learning natural science, the results of the study.